Biological control of Aphis fabae and Bemisia tabaci by the native isolates of Beauveria bassiana in Kerman province - Zamani, Zahra; Mehdi Aminaee, Mohammed; Bakhshi khaniki, Gholamreza (published online, 2012)
In this research, we isolated the pathogenic strain, KB512, of entomopathogenic fungi Beauveria bassiana from soil and insects, which produced aerial and submerged conidia and blastospores in the laboratory conditions. We investigated the best conditions for the production and utilisation of the spore suspension to spray Aphis fabae and Bemisia tabaci, which are two important pests in Kerman province (Iran). The pathogenicity test was carried out with direct spray. To bioassay the isolates, three concentrations of the spore suspension were prepared as follows: 1 6 10 8 , 1 6 10 7 and 1 6 10 6 conidia/ml. The pests were sprayed by aerial conidial suspension, which was prepared by 0.01% Tween-80 in distilled water, and the controls were sprayed by 0.01% Tween-80 in distilled water. After spraying the pests, the plates were incubated at 25 + 18C and 80% of relative humidity. Then the treated pests were monitored every day for the fungal growth and mortality. After nine days, mortality in the insects treated with 1 6 10 8 conidia/ml was 42.4% and 34% for Aphis fabae and Bemisia tabaci, respectively. Nowadays, biological control methods, especially the use of microbial agents, are believed to be environmentally friendly and safe for non-target organisms. Therefore, such biological agents can be mass produced to control the pests.
full tex
Keywords: Aphis fabae; Bemisia tabaci; Beauveria bassiana; biological control; entomopathogenic fungi